Polycrystalline nanowires of gadolinium-doped ceria via random alignment mediated by supercritical carbon dioxide - Kim, Sang Woo; Ahn, Jae-Pyoung (NATURE PUBLISHING GROUP, 2013)
This study proposes a seed/template-free method that affords high-purity semiconducting nanowires from nanoclusters, which act as basic building blocks for nanomaterials, under supercritical CO2 fluid. Polycrystalline nanowires of Gd-doped ceria (Gd-CeO2) were formed by CO2-mediated non-oriented attachment of the nanoclusters resulting from the dissociation of single-crystalline aggregates. The unique formation mechanism underlying this morphological transition may be exploited for the facile growth of high-purity polycrystalline nanowires.
Keywords: CEO2 NANORODS; OXIDE; GROWTH